Complete mitochodrial genome of Bangana decora (Cypriniformes, Cyprinidae). (3rd May 2016) - Li, Hong; Li, Chuanwu; Tang, Xiangbei; Liao, Fuchu; Wang, Chongrui; Liang, Zhiqiang; Liu, Hong; Yuan, Xiping
Abstract: The complete mitochondrial genome of Bangana decora was determined in this study. The gene composition, arrangement and transcriptional orientation in B. decora mitogenome were identical to most vertebrates. The complete mitogenome of B. decora was 16, 607 bp in size with 13 protein-coding genes, 22 tRNA genes and a control region. Two start codon patterns and three stop codon patterns were found in protein-coding genes. Only the tRNA-Ser2 could not fold into a typical clover-leaf secondary structure due to the absence of the dihydrouridine arm. Sequence alignment results suggest that the complete mitogenome of B. decora is an efficient tool to study molecular phylogenetics, biogeography and adaptive evolution of this lineage.